A closer look at the spectrum of drug-induced liver injury in sub-Saharan Africa. Issue 9 (2nd September 2019) - Riebensahm, Carlotta; Ka, Daye; Sow, Abdoul; Semmo, Nasser; Wandeler, Gilles
ABSTRACT: Introduction : Drug-induced liver injury (DILI) has become the most frequent cause of acute liver failure in high-income countries. However, little is known about the determinants of DILI in sub-Saharan Africa (SSA), where the prescription of antimicrobials and the use of potentially hepatotoxic traditional medicine are common. Areas covered : Based on an extensive literature search, we summarize current data available on the epidemiology and risk factors of DILI in SSA. We discuss the most likely causes of DILI in the region, including antimicrobial therapies and traditional medicine. We also highlight research gaps as well as barriers to diagnosis and management of the condition, and explore ways to address these important challenges. Expert opinion : DILI is underestimated in SSA and several factors challenge its early diagnosis, including lack of information on the causes of DILI in the region, sub-optimal knowledge about the condition among clinicians, and structural difficulties faced by health care systems. In order to better prevent the occurrence of DILI and its complications, it is crucial to enhance awareness among health care providers and patients, adapt drug prescription habits and regulations, and improve current knowledge on the main risk factors for DILI, including host genetic and environmental determinants.